Fiction and affect: Studies in the mid-twentieth century American novel and its utopian contexts - Millar, Darren (University of Ottawa (Canada), 2006)
This dissertation examines selected mid-Twentieth Century novels by four American writers (Carson McCullers, James Baldwin, William Styron, and Vladimir Nabokov) in order to offer a reappraisal of a difficult and often overlooked moment in the history of American fiction. Specifically, it considers how writers with liberal tendencies respond to the political inhibitions of a culture increasingly dominated by the consensus discourse of the Cold War. Rather than giving over to cynicism by adopting strictly apolitical themes, these writers demonstrate a commitment to liberal society through the values of tolerance, diversity, and a distinctively liberal openness to the future community. This optimistic way of reading of the often superficially bleak fiction of mid-century rests on a rejection of the common premise that the postwar moment marks the end of history, of ideology, and of utopia. I undertake this initiative by means of a theoretical engagement with the concepts of affect and utopia. First, I offer a reconsideration of the concept of utopia in order to understand how utopian thinking may survive the historicist crisis in which it becomes neither possible nor desirable to imagine a political alternative to the status quo. Postwar (or post-historicist) utopia does not depend on the articulation of a specific future state or goal but dwells in the potential for change and future possibility inherent in the present moment. This revision of utopia provides a unique opportunity to engage the mid-century novel, for the latter's preoccupation with the meaning of affective experience represents a similar attempt to locate social potential within the present moment. The various readings of mid-century American novels that follow collectively strive to express and explore the connection between the fictional treatment of affect and the unique terms and conditions of liberal utopia as it emerges in the context of mid-century American culture.
Keywords: Literature, American.